Optimizing Food Aid with the Communities of Getasan District, Salatiga, East Java (Experimental Student Experience, 2023)
Poverty has become a scary shadow in Indonesia. Many people continue to live in poverty, particularly on the Indonesian island of Java. Poverty has a direct impact on everyone. According to clause 34 of the Constitution of 1945, communal attention is required. As a result, the goal of this community activity is to deliver basic supplies to the community in Getasan District, Salatiga, Central Java, based on data obtained from the local government. A survey was conducted to determine distribution areas before giving 60 staple items every night for three days. As a consequence, 180 households received groceries, which made life easier.